Kinerja Pengelolaan Sampah Perkotaan di Kota Kecamatan Gresik - Rizaldi Putra Pratama; Tuhu Agung Rachmanto (Publikasi Indonesia, 2023)
Garbage is a problem that needs more attention. Increasing population density and limited land to accommodate leftover consumption are one of the factors causing the volume of waste to continue to mount. This study aims to determine the performance of urban waste management in the city of Gresik sub-district. The analysis technique used in this study is a qualitative and quantitative descriptive analysis technique. The technique used to select respondents is Stratified Random Sampling technique. The data used uses primary and secondary data. The results showed that there was 281.61 m3 of waste per day, with 5.1 m3 per day coming from the non-residential sector and 21 villages/kelurahan in Gresik District. The value of the performance level of waste management in Gresik District is 56% of the average yield for each waste management variable, so that the performance level of waste management in Gresik District is quite good. Performance results are influenced by technical, institutional, financing, community and private aspects as well as laws and regulations. Factors affecting the performance of waste management include transportation operations that are not optimal as a whole, the number of personnel and infrastructure is still limited, the community does not fully support waste management and there is still a lack of enforcement against violations of waste regulations.